2019
DOI: 10.1371/journal.pgen.1008451
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive role of E-cadherin in maintaining prostatic epithelial integrity during oncogenic transformation and tumor progression

Abstract: E-cadherin complexes with the actin cytoskeleton via cytoplasmic catenins and maintains the functional characteristics and integrity of the epithelia in normal epithelial tissues. Lost expression of E-cadherin disrupts this complex resulting in loss of cell polarity, epithelial denudation and increased epithelial permeability in a variety of tissues. Decreased expression of E-cadherin has also been observed in invasive and metastatic human tumors. In this study, we investigated the effect of E-cadherin loss in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
(68 reference statements)
1
19
0
Order By: Relevance
“…Therefore, the increased expression of CD44 in the coinfected group might be due to the presence of EBV. Based on the findings, co-presence HPV/EBV infection or mono-infection is probably can contribute to these changes (i.e., E-cadherin, N-cadherin, Twist, PTPN13, Slug, CD44, Bcl-2, and Survivin), but further experimental studies are needed to prove the role of viral infections in the regulation of Anoikis molecular pathways and metastasis in PCa [ 73 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increased expression of CD44 in the coinfected group might be due to the presence of EBV. Based on the findings, co-presence HPV/EBV infection or mono-infection is probably can contribute to these changes (i.e., E-cadherin, N-cadherin, Twist, PTPN13, Slug, CD44, Bcl-2, and Survivin), but further experimental studies are needed to prove the role of viral infections in the regulation of Anoikis molecular pathways and metastasis in PCa [ 73 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, occludin is commonly used to identify tight junctions, that controls the paracellular passage creating a regulable semi permeable diffusion barrier between individual cells. Thus, when the tight junction integrity is affected, periodontitis infections might find a better homing situation in case [15]; E-cadherin is a desmosome marker and its proper expression is essential to maintain the integrity of the epithelium [50], as well as β-catenin, a protein that localizes in the adherents junctions [51]. In the present study, different β-catenin expression suggested that the machined surface induce impaired cell to cell interaction, adversely affecting proper expression of both tight and adherent junctions, as well as desmosomes, while the laser-treated one do not influence the right organization of the junctional epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations and the supporting literature revealed a structural loss of tissue architecture and loss of epithelial polarity in the presence of PAF, indicating that such phenotypes are important components toward the maintenance of polarity and disruption of these leads to transformation and gives direct evidence in cancer development and progression (Lee and Vasioukhin, 2008). E-cadherin, a cell-cell junction protein is known to maintain epithelial polarity by being a center for the intercommunicating signals between catenins and the cytoskeletal network and disruptions in this contact lead to various morphogenetic and developmental defects apart from loss of epithelial polarity (Olson et al, 2019). E-cadherin complexes with cytoplasmic β-catenin at the junctions and aberrations in this interaction leads to an increased flux of cytoplasmic β-catenin resulting in transformation and such an observation is commonly noted in solid tumors and epithelial cancers (Kourtidis et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin, a cell-cell junction protein is known to maintain epithelial polarity by being a center for the intercommunicating signals between catenins and the cytoskeletal network and disruptions in this contact lead to various morphogenetic and developmental defects apart from loss of epithelial polarity ( Olson et al, 2019 ). E-cadherin complexes with cytoplasmic β-catenin at the junctions and aberrations in this interaction leads to an increased flux of cytoplasmic β-catenin resulting in transformation and such an observation is commonly noted in solid tumors and epithelial cancers ( Kourtidis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%